(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Pharmaceutical care has been promoted as one of the core goal of pharmacy profession’s, but its execution in many developing nations has been unsatisfactory but in most of the developed countries, Pharmaceutical Care is already a reality and has demonstrated efficacy in reduction of worsening the chronic diseases and in the cost of the health system Objective: The general objective of the study was to explore pharmacist preparedness, attitude and skills towards adoption of novel elements of pharmaceutical care in Pakistan. Method: A descriptive cross-sectional study design was used. Sample size was calculated using Raosoft calculator at confidence level of 95% and margin of error of 5% and sample size calculated comes out to be 382. Convenience sampling technique was used for selection of respondents for this study. Questionnaires were self-administered and collected on the same day to avoid biasness. The data was cleaned, coded and entered in SPSS after data collection. Mann-Whitney and Kruskal Wallis (p ≥ 0.05) tests were applied according to different demographic variables. Result: No significant difference (p ≥ 0.05) was seen in knowledge and preparedness of pharmacist with respect to gender, setting, age, education, income and experience. However, significant difference (p ≥ 0.05) was seen in preparedness of pharmacist with respect to setting. Hospital pharmacist had relatively better knowledge and preparedness. Conclusion: The current study concluded that pharmacists had adequate knowledge and skills regarding pharmaceutical care, but their attitude toward the implementation of pharmaceutical care was negative. The study concluded that both hospital and community pharmacists were under prepared for the adaptation of novel elements of pharmaceutical care. Hospital pharmacists had comparatively better preparedness than community pharmacists regarding pharmaceutical care. Trainings should be conducted to improve the pharmacist preparedness, attitude and skills towards adoption of novel elements of pharmaceutical care in Pakistan.